Early emergency department discharge for intermediate heart score patients presenting for chest pain - Amber Pawlikowski; Elizabeth Hubbard; Joel Krauss; Javier Valle; Jessica Doan; Susanne DeMeester; Bradley Hubbard (Journal of the American College of Emergency Physicians Open)
Abstract Study Objective The use of the HEART score to risk stratify patients for short‐term major adverse cardiac events in the emergency department (ED) setting is well established. Although discharge to home for low‐risk HEART score patients is widely accepted as safe practice, there are limited outcomes data on moderate‐risk HEART score patients discharged to home. We investigated the safety of discharging moderate‐risk HEART score patients to home from the ED with established early cardiology follow‐up. Methods We performed a retrospective cohort analysis of patients presenting to the ED with chest pain from April 2020 through December 2020. Patients were evaluated in the ED and underwent serial conventional troponin testing and electrocardiogram (ECG). Clinicians calculated a HEART score and employed shared decision‐making with moderate‐risk patients (score 4–6), offering hospital admission versus discharge home with a formalized process for rapid cardiology follow‐up (within 2 business days). We assessed the frequency of acute myocardial infarction or death at 30 days and before cardiology follow‐up. Results During our study period, 2939 patient encounters were screened for chest pain. Of these, 333 of 547 eligible moderate‐risk HEART score patients were referred for rapid follow‐up. The median time to follow‐up appointment was 2.9 business days (interquartile range 1.3, 6.5), and 264 (79%) of patients kept their follow‐up appointment. One patient (0.3%) suffered death within 30 days, before cardiology follow‐up. There were no myocardial infarctions. Conclusions These results suggest that moderate‐risk HEART score patients may be considered for discharge from the ED with rapid cardiology follow‐up. Formalizing processes to facilitate these early evaluations may represent a viable alternative to hospital admission, without diminishing patient outcomes.